A Comparative Study of Analgesic Effect of Intrathecal Nalbuphine and Fentanyl as Adjuvant in Lower Limb Orthopaedic Surgery - Shagufta Naaz; Usha Shukla; Swati Srivastava; Erum Ozair; Adil Asghar (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Intrathecal opioids when added to local anaesthetics decrease their dosage and provide haemodynamic stability. Nalbuphine is an agonist-antagonist and acts on kappa receptors providing analgesia. Aim: The study aims to compare the analgesic efficacy of fentanyl with that of two doses of nalbuphine when used with injection bupivacaine heavy in spinal anaesthesia. Materials and Methods: A randomised, double blinded, prospective study on 90 patients of ASA I and II undergoing lower limb orthopaedic surgery under subarachnoid block was done. Patients were randomly allocated into three groups (n=30). Each group received 12.5 mg of 0.5% of injection bupivacaine heavy along with either 25 µg of 0.5 ml fentanyl (Group F) or 0.8 mg of 0.5 ml nalbuphine (Group NL) or 1.6 mg of 0.5 ml nalbuphine (Group NH). Characteristics of sensory and motor blocks, haemodynamic changes, duration and quality of analgesia, adverse effects, sedation, VRS score and analgesic requirement were studied at different time interval intraoperatively and till 24 hours of block. Results: The duration of analgesia (in minute) was 441±119.69 in NL Group, 450±103.38 in NH Group and 300.0±88.53 in Group F (p=0.05). There was no significant difference regarding block characteristics and haemodynamic parameters. Total 24 hours analgesic requirement was titrated by analgesic score which was 2.25±0.7 (NH Group), 1.875±0.83 (NL Group) and 3.375±1.77 (F Group) p=0.0186 by ANOVA. The adverse effects of NL Group were least. Conclusion: There was no significant advantage of intrathecal fentanyl or 1.6 mg nalbuphine over low dose 0.8 mg nalbuphine.